2015
DOI: 10.1002/jqs.2786
|View full text |Cite
|
Sign up to set email alerts
|

Shallow-marine deposits associated with the 2011 Tohoku-oki tsunami in Sendai Bay, Japan

Abstract: Little is known about offshore tsunami deposits, although they have the potential to improve palaeotsunami reconstructions, especially in areas with limited preservation of onshore tsunami deposits. We analysed 44 sediment cores collected in 2012 at water depths of 14–30 m in Sendai Bay, north‐eastern Japan, to identify the deposits of the 2011 Tohoku‐oki tsunami with the aid of 134Cs released from the Fukushima‐Daiichi Nuclear Plant. The preserved tsunami deposits in the inner shelf are interbedded with very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 20 publications
2
36
0
1
Order By: Relevance
“…Unit D is dominated by thick-bedded, parallel and crosslaminated, calcareous fine to medium-grained, well-sorted, often argillaceous, very sandy limestones, or calcareous quartz sandstones, interbedded with sporadic thin calcareous shales. Graded beds show consistent trends from parallel lamination to festoon (hummocky) cross-lamination typical of deposits of waning storms or tsunamis ( Figure 5B) (Brookfield et al, 2013;Tamura et al, 2015). Most of the quartz grains are angular to sub-rounded and first-cycle ( Figure 4B, 4), but a few are very well-rounded, indicating a desert source for those (Nakazawa et al, 1975).…”
Section: Guryul Ravine Sectionmentioning
confidence: 81%
“…Unit D is dominated by thick-bedded, parallel and crosslaminated, calcareous fine to medium-grained, well-sorted, often argillaceous, very sandy limestones, or calcareous quartz sandstones, interbedded with sporadic thin calcareous shales. Graded beds show consistent trends from parallel lamination to festoon (hummocky) cross-lamination typical of deposits of waning storms or tsunamis ( Figure 5B) (Brookfield et al, 2013;Tamura et al, 2015). Most of the quartz grains are angular to sub-rounded and first-cycle ( Figure 4B, 4), but a few are very well-rounded, indicating a desert source for those (Nakazawa et al, 1975).…”
Section: Guryul Ravine Sectionmentioning
confidence: 81%
“…) collected within and at the base of L1 and L2, did not contain enough foraminifera specimens to be considered statistically representative of the study sample as confirmed by very low values in BFN. Indeed, this reduction of foraminifera can be interpreted as related to a major input of fine sediments, as also observed elsewhere in modern offshore tsunami samples collected close to the shelf‐break (Ikehara et al ., ; Tamura et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…After the 2004 Indian Ocean and 2011 Tohoku‐oki tsunamis, offshore surveys were conducted to collect material, mainly from the inner continental shelf [0 to 30 m below sea level (bsl)] and over the shelf‐break (>100 m bsl). These studies highlighted that in the marine realm the tsunami‐related units are subjected to the action of currents, waves and bioturbation that occur immediately after their deposition (Feldens et al ., ; Sakuna et al ., ; Ikehara et al ., ; Tamura et al ., ; Yoshikawa et al ., ; Seike et al ., ). Thus, it is often not easy to recognize offshore tsunami deposits even when they are related to recent events or with a precise age control (Toyofuku et al ., ) because of their potentially low preservation in shallow water due to reworking and transport by currents, waves (Weiss & Bahlburg, ) and gravity flows which disperse sediment on the continental shelves.…”
Section: Introductionmentioning
confidence: 99%
“…They are well preserved as anomalous coarse layers in peat or mud deposits typical of low-energy terrestrial or shallow-seabed environments (Atwater, 1992;Bourgeois et al, 1988;Dawson & Stewart, 2007;Monecke et al, 2008;Sawai et al, 2015;Seike et al, 2016Seike et al, , 2017a. Although tsunami deposits might be modified or obliterated by subsequent physical (Shinozaki et al, 2015;Szczuci nski, 2012;Tamura et al, 2015) and/or biological processes (Seike et al, 2016), they can remain for long periods in calm coastal embayments (Seike et al, 2017a). This indicates that tsunamis have semipermanent effects on the seafloor topography and the grain-size composition of seafloor sediments; in other words, tsunami sedimentation is a short-term phenomenon that has a major effect on the benthic environment over the longer term.…”
Section: Introductionmentioning
confidence: 99%